The World Conference on Human Rights: still a guiding light a quarter of a century later. Issue 3 (2nd September 2019) - Anthony, Dorothea
ABSTRACT: The 1993 World Conference on Human Rights (World Conference) and its Vienna Declaration and Programme of Action remain as instrumental to international human rights law and discourse in today's world as they were in the aftermath of the Cold War, chiefly because the World Conference's underlying ideologies remain relevant. Despite its formal commitment to the indivisibility principle, the World Conference promulgated ideas that were products of global post-Cold War economic conditions, including civil and political rights, democracy, and liberalism. Current conditions continue to reinforce these ideas. Indeed, as long as these conditions persist, the human rights community is likely to embrace the "Viennese" concept of rights.